BENTUK RELASI KUASA DALAM PENGELOLAAN RESOR WISATA NUSA DUA, BALI - I Gusti Ketut Purnaya (Institut Pariwisata dan Bisnis Internasional, 2015)
Nusa Dua Tourist Resort has been an important part of the development and growth of tourism industry in Indonesia in general and in Bali in particular. The development in Nusa Dua Area has caused many parties with their respective interests to struggle for its management. This research focuses on the struggle of the three pillars for power relation in the management of Nusa Dua Tourist Resort. The three pillars include the government, in this case, BTDC, the investors, and the local people. Therefore, the presents study was intended to analyze and answer the following questions: what was the form of the power relation among the three stakeholders such as the government, the investors, and the local people in the management of the Nusa Dua Tourist Resort from the developing period until 2014. The result of the study showed that the power relation in the management of the Nusa Dua Tourist Resort was affected by the hegemonic power, the negotiation power, and the oppositional power/counter hegemonic. Â